Optomechanics of Chiral Dielectric Metasurfaces. Issue 4 (18th December 2019) - Zanotto, Simone; Tredicucci, Alessandro; Navarro‐Urrios, Daniel; Cecchini, Marco; Biasiol, Giorgio; Mencarelli, Davide; Pierantoni, Luca; Pitanti, Alessandro
Abstract: The coupling between electromagnetic fields and mechanical motion in micro‐ and nanostructured materials has recently produced intriguing fundamental physics, such as the observation of mesoscopic optomechanical phenomena in objects operating in the quantum regime. It is also yielding innovative device applications, for instance in the manipulation of the optical response of photonic elements. Following this concept, here it is shown that combining a nanostructured chiral metasurface with a semiconductor suspended micromembrane can open new scenarios where the mechanical motion affects the polarization state of a light beam, and vice versa. Optical characterization of the fabricated samples, assisted by theory and numerical modeling, reveals that the interaction is mediated via moving‐boundary and thermoelastic effects, triggered by intracavity photons. This work represents a first example of "Polarization Optomechanics, " which can give access to new forms of polarization nonlinearities and control. It can also lead to wide applications in fast polarimetric devices, polarization modulators, and dynamically tunable chiral state generators and detectors. Abstract : Handling light polarization—and light chirality—in a subwavelength, lossless, and dynamical fashion is a task which is addressed in this work by appropriately engineering a mechanically compliant and optically resonant semiconductor patterned membrane. Given the ubiquity of polarized light in applied sciences, the studied device may prove useful in fields such as biophotonics, material science, drug discovery, and telecommunications.